Physical Risk Factors And Observational Tools For Computer Office Workers–An Overview - Halim, Isa; Radin Umar, Radin Zaid; Padmanathan, Vinothini; Too, Yi Wei (IAEME Publication, 2018)

(untitled)
In conjunction with the Industry 4.0,the computer usage among office workers had increased tremendously in past recent years.The recent technology development with a different type of pointing devices had exposed the computer office workers with a different type of physical risk factors associated with work related musculoskeletal disorders (WRMDs).Although a different type of observational tools were existed to identify the physical risk factors among computer office workers,however the prevalence rate of WRMDs among computer office workers are still increasing.Hence,the aim of the current study was to provide an overview of physical risk factors that were associated with the development of WRMDs among computer office workers.In addition,the paper also discussed on the preexisting paper and pen observational tools that were used previously to identify the risk factors of WRMDs among computer office workers.In conclusion,physical risk factors of WRMDs among computer office workers were consists of task,environmental and technology/equipment factors.None of the paper and pen ergonomic observational tools cover the entire physical risk factor that causes the WRMDs among computer office workers.In addition,the majority of the tools were not validated.Hence,the information from the current study can help the respective agencies to develop a new and validated ergonomic paper and pen observational tool that covers the entire physical risk factors (task, environmental and technology/equipment factors) that associated with the development of WRMDs among computer office workers.